The efficacy of retrograde intra-renal surgery (RIRS) for lower pole stones: results from 2946 patients - TANIDIR, YILÖREN (My University, 2023)
Purpose: To evaluate the perioperative outcomes of retrograde intra-renal surgery (RIRS) for lower pole stones (LPS) and factors affecting stone-free rate (SFR). Methods: Data from 20 centers were retrospectively reviewed. Inclusion criteria were adult patients, normal renal anatomy, and LPS. Exclusion criteria were bilateral surgery, concomitant surgery for ureteral stones. SFR was defined as a single residual fragment (RF) ≤ 2 mm and evaluated 3-months after surgery. A multivariable logistic regression analysis was performed to assess factors associated with RF. Statistical significance was set at p value < 0.05. Results: 2946 patients were included. Mean age and stone size were 49.9 years 10.19 mm, with multiple LPS in 61.1% of cases. Total operation and laser time were 63.89 ± 37.65 and 17.34 ± 18.39 min, respectively. Mean hospital stay was 3.55 days. Hematuria requiring blood transfusion and fever/urinary infections requiring prolonged antibiotics occurred in 6.1% and 169 5.7% of cases, while sepsis with intensive-care admission in 1.1% of patients. On multivariate analysis, Multiple stones (OR 1.380), stone size (OR 1.865), and reusable ureteroscopes (OR 1.414) were significantly associated with RF, while Thulium fiber laser (TFL) (OR 0.341) and pre-stenting (OR 0.750) were less likely associated with RF. Conclusions: RIRS showed safety and efficacy for LPS with a mean diameter of 10 mm. This procedure can achieve a satisfactory SFR in pre-stented patients with a single and smaller stone, particularly with TFL use.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; Endourology; Laser lithotripsy; Lower polar stones; Nephrolithiasis; Retrograde intra-renal surgery; Nephrolithiasis; Retrograde intra-renal surgery; Lower polar stones; Endourology; Laser lithotripsy